Analysis of liver miRNA in Hu sheep with different residual feed intake - Lin, Changchun; Wang, Weimin; Zhang, Deyin; Huang, Kai; Zhang, Yukun; Li, Xiaolong; Zhao, Yuan; Zhao, Liming; Wang, Jianghui; Zhou, Bubo; Cheng, Jiangbo; Xu, Dan; et al. (Frontiers in Genetics, 2023)
Feed efficiency (FE), an important economic trait in sheep production, is indirectly assessed by residual feed intake (RFI). However, RFI in sheep is varied, and the molecular processes that regulate RFI are unclear. It is thus vital to investigate the molecular mechanism of RFI to developingcultivation a feed-efficient animal breedsheep. The miRNA-sequencing (RNA-Seq) was utilized to investigate miRNAs in liver tissue of 6 out of 137 sheep with extreme RFI phenotypic values. In these animals, as a typical metric of FE, RFI was used to distinguish differentially expressed miRNAs (DE_miRNAs) between animals with high (n = 3) and low (n = 3) phenotypic values. A total of 247 miRNAs were discovered in sheep, with four differentially expressed miRNAs (DE_miRNAs) detected. Among these DE_miRNAs, three were found to be up-regulated and one was down-regulated in animals with low residual feed intake (Low_RFI) compared to those with high residual feed intake (High_RFI). We identified 247 miRNAs and four DE_miRNAs (three up-regulated and a down-regulated in Low_RFI versus High_RFI animals) in sheep. The target genes of DE_miRNAs were primarilymainly associated with metabolic processes and biosynthetic process regulation; . Furthermoreadditionally, they were also considerablysignificantly enriched in the FE related to glycolysis, protein synthesis and degradationdecomposition, and amino acid biosynthesis pathways. Six genes were identified by co-